Synthesis of Novel Derivatives of Dissymmetric Bisarylidene of Tetrahydro-4H-pyran-4-one - Abaee, Mohammad Saeed; Afshinpoor, Leila; Mojtahedi, Mohammad Majid (Current Organic Chemistry, 2025)
Several studies have reported that aldol condensation of various cyclic and acyclic ketones with aromatic aldehydes leads to the formation of symmetrical bisarylidene derivatives, while efficient synthesis of mono- and dissymmetric bisarylidenes is not very common and only a limited number of related reports are available. In the present work, a new one-pot method is designed and performed to synthesize dissymmetric bisarylidene derivatives of tetrahydro-4H-pyran-4-one heterocyclic system. Under the optimized conditions, the first aldehyde reacts with the starting ketone to give the corresponding monoarylidene. This monoarylidene can be either isolated as product 2 or used as the intermediate for a subsequent condensation with the second aldehyde to produce the respective derivative of 3. Both steps can take place in one pot, and high yields of either the monoarylidene intermediates or the final dissymmetric bisarylidene products would be obtained in short time intervals. The method is amenable to the synthesis of both mono- and dissymmetric bisarylidenes of the target compounds. New products of the reaction are fully characterized based on their 1H NMR, 13C NMR, IR, and mass spectroscopic data. The purity of these products is confirmed by elemental analyses. The results are promising to expand the outcome by applying the conditions to the synthesis of the respective derivatives of other heterocyclic systems.
Keywords: aldol condensation